Analisis Strategi Bersaing Pada Toko Kue Khas Kutai Hj. Fatimah Di Tenggarong - Ari Ramadhan; Iskandar Iskandar; Erwinsyah Erwinsyah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:Sales of snack products that are quite fast in Kutai Kartanegara Regency is a cake sales business. Cake sales business is a prospective business and can be easily developed in accordance with the needs of the community. Cake sales is a pretty bright business prospect and much in demand by the community.          One of the well known cake seller business in Tenggarong City is Cake Shop Typical Of Kutai Hj.Fatimah in Tenggarong at road Kramajaya Kel.Mangkurawang Tenggarong Kab. Kutai Kartanegara. Researchers are interested in conducting research on Cake Shop Typical Of Kutai Hj.Fatimah in Tenggarong because it wants to know how competitive the strategy faced by the business if it is compared with other Modern Cake Stores.          Cake Shop Typical Of Kutai Hj.Fatimah in Tenggarong is home-based and is produced by involving several workers (homeowners) and with affordable raw materials to produce the cake. As for the process of selling the cakes only in the offer to the consumer in front of the front kiosk Hj.Fatimah mother's house only on Jalan Krama Jaya Mangkurawang Village.          The current problem that exists in Cake Shop Typical Of Kutai Hj.Fatimah in Tenggarong is still a bit dominating market share and still the influence of other cake business competitors that hinder the increase of sales. In this case Cake Shop Typical Of Kutai Hj.Fatimah in Tenggarong not yet know the techniques of competing strategy in seizing market share, especially traditional cakes. While other competitors have been able to master the market share by peddling modern cakes, so this becomes a challenge for business actors manufacturing traditional cakes. Keywords: Competitive Strategy Analysis, SWOT Method